2011
DOI: 10.1039/c0cp02821e
|View full text |Cite
|
Sign up to set email alerts
|

Influence of excited state aromaticity in the lowest excited singlet states of fulvene derivatives

Abstract: The absorption spectra and excited state dipole moments of four differently substituted fulvenes have been investigated both experimentally and computationally. The results reveal that the excited state dipole moment of fulvenes reverses in the first excited singlet state when compared to the ground state. The oppositely polarized electron density distributions, which dominate the ground state and the first excited singlet state of fulvenes, respectively, reflect the reversed π-electron counting rules for arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
82
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 61 publications
(87 reference statements)
4
82
0
2
Order By: Relevance
“…Furthermore, Ottosson and colleagues observed the aromatic chameleon spectroscopic features of fulvene based on sensitization, in accord with their previous theoretical model 7,25,26 . Later it was shown through experimental studies involving solvatochromatic shifts that the S 1 states of the substituted fulvenes display similar effects in the corresponding T 1 states 7, 27 . In addition to their work with fulvenes, this same research team recently reported on the basis of computational calculations that various substituted cyclopentadienes and siloles would display aromatic chameleon features 28 .…”
mentioning
confidence: 97%
“…Furthermore, Ottosson and colleagues observed the aromatic chameleon spectroscopic features of fulvene based on sensitization, in accord with their previous theoretical model 7,25,26 . Later it was shown through experimental studies involving solvatochromatic shifts that the S 1 states of the substituted fulvenes display similar effects in the corresponding T 1 states 7, 27 . In addition to their work with fulvenes, this same research team recently reported on the basis of computational calculations that various substituted cyclopentadienes and siloles would display aromatic chameleon features 28 .…”
mentioning
confidence: 97%
“…Recently, Kim and Osuka characterized the excited-state (anti)aromaticity in expanded porphyrins [17][18][19][20][21][22] . Ottosson and co-workers reported a series of "aromatic chameleons" that are prone to be aromatic in both the T 1 and S 1 states [23][24][25][26][27] . Note that Baird's rule can also be applied to the S 1 state [28][29][30] .…”
mentioning
confidence: 99%
“…16 More recently, excited state aromaticity has been found in the lowest-lying singlet excited state of fulvene derivatives. 17 It is usually accepted that 4nπ-electron monocycles are aromatic not only in the T 1 (Baird's rule) but also in the S 1 state. Finally, let us mention the work by Soncini and Fowler that represents a generalized form of Baird's rule.…”
mentioning
confidence: 99%